Congenital Rubella Syndrome Surveillance After Measles Rubella Vaccination Introduction in Yogyakarta, Indonesia. Issue 12 (7th September 2021) - Herini, Elisabeth Siti; Triono, Agung; Iskandar, Kristy; Prasetyo, Ashadi; Nugrahanto, Andika Priamas; Gunadi,
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Congenital rubella syndrome (CRS) is a fatal disease causing severe congenital defects. Indonesia had the highest CRS cases in the world in 2016 with a commitment to achieve elimination of rubella disease by 2020, through the campaign and introduction of measles rubella (MR) national vaccination program in 2017 and 2018. This study aimed to describe the impact of the national vaccination campaign by conducting surveillance of CRS cases and comparing the incidence of new CRS cases before and after the MR vaccination campaign. Methods: From July 2015 to July 2020, we conducted surveillance of CRS in Yogyakarta. Suspected patients underwent complete clinical examinations. Serology was tested for the presence of IgM and IgG antibodies against rubella. Descriptive analysis was used to characterize the demographic and clinical characteristics of the cases before and after the MR vaccination campaign. Results: The study involved 229 infants who were suspected for CRS. Laboratory-confirmed cases were found in 47 of them (20.86%). Most of the laboratory-confirmed cases (55.3%) were reported among 1–5 months old infants. Common clinical features among laboratory-confirmed cases included structural heart defects in 43 (91.4%). There was a significant decrease (60.9%) of CRS incidence from 0.39 per 1000 live births in the precampaign era to 0.08 in the postcampaign era ( P = 0.00). Conclusion: There has been a significant declining number of CRS cases based on pre- and post-MR vaccination campaign in Yogyakarta, Indonesia. An effective surveillance system will help monitor the number of CRS cases.